H??bito no consumo, rolagem da d??vida e penalidade no mercado de cr??dito - Monteiro, Marcel Stanlei (2014)
This research investigated the existence of representative agents ' consumption habit of the Brazilian economy, using for this purpose, the model of Dubey, Geanakoplos and Shubik (2005), which received the incorporation of a term that represents the penalty applied to agents who take credit and subsequently missing with their financial commitments. It was used the model known as the Consumption-Based Capital Asset Pricing Model-CCAPM, to assign to the model of Dubey, Geanakoplos and Shubik (2005) generalization of infinite periods, instead of just two periods. Thus, to meet the objectives of this research, it has been estimated, through two utility functions, using the Generalized Method of Moments GMM, the inter-temporal discount factor consumption, also known as the impatience of the agents, the coefficient of relative risk aversion and the parameter that governs the separability of the time consumption. In addition, the penalty rate was calculated and, also, the scroll rate of these agents, debt relating to these calculations and estimates, information on the Brazilian economy, since 2000, making it possible to conclude that, for the period under examination, existed the habit in the consumption of representative agents, all of whom were penalized whenever preferred not to pay their obligations, which occasioned in the scrolling your debt. In addition, it was concluded that these agents are impatient and risk-averse and, also, that the important role played credit to contribute to growth and economic development.